Representasi Menuju Penerapan Era Normal Baru Pada Sampel Koran Tempo Edisi 27 Mei 2020 - Maulida, Dwinny Sukma; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Information regarding the implementation of the New Normal Era during the Covid-19 pandemic announced by President Joko Widodo has brought pros and cons. Tempo newspaper as a mass media raised the issue in the form of a caricature illustration on the front cover of Tempo newspaper on 27 May 2020. The purpose of this study is to explain the representation of the implementation of the New Normal Era in Tempo newspaper on 27 May 2020. This research was conducted using the method interviews and semiotic analysis proposed by Charles Sanders Pierce with qualitative research types and constructivist paradigms. The results of this study, Koran Tempo represents the application of the New Normal Era in the caricature illustration of the competition arena. there is a meaning contained in each caricature illustration, based on this Tempo has displayed the function of caricatures as a medium for delivering messages. Keywords: Tempo newspaper, Caricature, New Normal Era, Representation